Os Joelhos! Os Joelhos! Protective Embodiment and Occasional Injury in Capoeira - Delamont, Sara; Ribeiro Duarte, Tiago; Lloyd, Issie; Stephens, Neil (Frontiers in Sociology, 2021)
Capoeira, the African-Brazilian dance and martial art has enthusiastic devotees in Britain. Most practitioners are acutely aware of their capoeira embodiment, and have strategies to protect themselves from injury, and ways to seek treatment for any injuries they get. Drawing on data from a long-term ethnography and a set of 32 open-ended interviews with advanced students, the paper explores student strategies to prevent capoeira injuries, and their discoveries of effective remedies to recover from them, before it presents an analysis of their injury narratives using Frank’s three-fold typology of illness narratives. The capoeira study therefore adds to the research on sports and dance injuries, and to the intellectual debates on the nature of narrative in research on illness and injury as well as exploring one aspect of the culture of capoeira students in the UK.